2017
DOI: 10.1007/s11060-017-2511-z
|View full text |Cite
|
Sign up to set email alerts
|

Early tumor growth between initial resection and radiotherapy of glioblastoma: incidence and impact on clinical outcomes

Abstract: Early tumor growth, or increased contrast-enhancing tumor not related to evolving post-surgical injury, in the interval between surgical resection and initiation of radiotherapy has implications for treatment planning and clinical outcomes. In this study we evaluated the incidence of early tumor growth, correlated tumor growth with survival outcome measures, and assessed predictors of early tumor growth in glioblastoma. We reviewed the records of patients with newly-diagnosed glioblastoma who underwent surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…About half of the patients (46/90; 51%) progressed between surgery and initiation of adjuvant RT, regardless of waiting time to RT initiation. High incidence of REP and reports of overall survival are in accordance with other retrospective published studies [10][11][12]. The only one clinical negative predictive factor for the development of REP in our cohort was non-radical surgery, confirming the overall prognostic value of surgical radicality in glioblastoma [1].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…About half of the patients (46/90; 51%) progressed between surgery and initiation of adjuvant RT, regardless of waiting time to RT initiation. High incidence of REP and reports of overall survival are in accordance with other retrospective published studies [10][11][12]. The only one clinical negative predictive factor for the development of REP in our cohort was non-radical surgery, confirming the overall prognostic value of surgical radicality in glioblastoma [1].…”
Section: Discussionsupporting
confidence: 92%
“…REP diagnosis is based on a comparison of early postoperative MRI findings (up to 72 h postoperatively) and planning pre-RT MRI. Only a few studies retrospectively evaluated REP and indicated almost up to 50% risk of development of REP, regardless of the waiting time until the start of radiotherapy (RT) [10][11][12]. Clearly, these patients biased previous clinical trials, where no routine pre-RT MRI examination was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wee et al [9] have reported a significant incidence of 19.3% of IPD using two separate MRIs taken during the SRI in glioblastoma patients, and have recommended the routine use of additional pre-RT MRIs for disease evaluation and accurate RT-target delineation. The rapid growth of glioblastoma in a short-term interval has been confirmed by other investigators as well [10][11][12][13][14]. However, no study has investigated on the growth dynamics of AGs, particularly, the incidence of IPD during SRI.…”
Section: Introductionmentioning
confidence: 75%
“…The natural growth of glioblastoma evaluated by MRIs during the SRI has been studied by several investigators [9][10][11][12]. Pirzkall et al [11] reported that increase in volume or new onset of contrast-enhancement occurred in 53% of glioblastoma patients during the SRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation